The analysis of productivity and profitability in the CEE region: Focus on the private and public sector - Mijić, Kristina; Jakšić, Dejan; Berber, Nemanja (Serbian Journal of Management, 2015)
This paper presents a comparative analysis of productivity and profitability of companies of the private and public sector from selected countries of Central and Eastern Europe (CEE). The research is based on the data of productivity and profitability from "Cranet" project. The results of analysis indicate a statistically significant difference in the level of productivity and profitability between these two sectors, so that private sector has significantly higher level of productivity and profitability than the public sector companies. Analysis according to the individual countries also points to a significantly higher level of productivity and profitability in the private sector, except in Slovenia where the public sector companies have a better level only of productivity compared to the private sector.